2020
DOI: 10.1002/jcp.30161
|View full text |Cite
|
Sign up to set email alerts
|

Morphine promotes tumorigenesis and cetuximab resistance via EGFR signaling activation in human colorectal cancer

Abstract: Morphine, a mu‐opioid receptor (MOR) agonist, has been extensively used to treat advanced cancer pain. In particular, in patients with cancer metastasis, both morphine and anticancer drugs are given simultaneously. However, evidence showed that morphine might be a risk factor in promoting the tumor's malignant potential. In this study, we report that treatment with morphine could activate MOR and lead to the promotion of proliferation, migration, and invasion in HCT116 and DLD1 colorectal cancer (CRC) cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…A number of MOR agonists, such as morphine, have been reported to be effective in alleviating severe pain; however, there were obvious limitations, such as they are prone to abuse, which is associated with an increased, risk of overdose, and serious side effects ( 30 ). In addition, several studies on morphine have shown that it promotes the proliferation, apoptosis, migration, and invasion in the breast ( 22 , 31 ), lung ( 6 , 32 , 33 ) and colorectal cancer cell lines ( 34 ), and a few studies indicated that morphine has an anti-tumor effect ( 35 , 36 ). Its potential mechanisms include the promotion of tumor angiogenesis, cell cycle arrest, and apoptosis of cancer cells ( 22 , 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of MOR agonists, such as morphine, have been reported to be effective in alleviating severe pain; however, there were obvious limitations, such as they are prone to abuse, which is associated with an increased, risk of overdose, and serious side effects ( 30 ). In addition, several studies on morphine have shown that it promotes the proliferation, apoptosis, migration, and invasion in the breast ( 22 , 31 ), lung ( 6 , 32 , 33 ) and colorectal cancer cell lines ( 34 ), and a few studies indicated that morphine has an anti-tumor effect ( 35 , 36 ). Its potential mechanisms include the promotion of tumor angiogenesis, cell cycle arrest, and apoptosis of cancer cells ( 22 , 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies on morphine have shown that it promotes the proliferation, apoptosis, migration, and invasion in the breast ( 22 , 31 ), lung ( 6 , 32 , 33 ) and colorectal cancer cell lines ( 34 ), and a few studies indicated that morphine has an anti-tumor effect ( 35 , 36 ). Its potential mechanisms include the promotion of tumor angiogenesis, cell cycle arrest, and apoptosis of cancer cells ( 22 , 34 , 36 ). Agonists for the KOR, such as nalbuphine, have been shown to provide similar analgesic effects comparable to morphine, suppressing various acute or chronic pain and cancer pain effectively, and reducing morphine-related side effects such as respiratory depression, addiction ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis indicated that six pathways were significantly enriched in the high-risk group, including axon guidance, GnRH signaling, MAPK signaling, melanogenesis, vascular smooth muscle contraction, and VEGF signaling pathways. All six of these pathways have been associated with poor prognosis for CRC ( Je et al, 2013 ; Zhu et al, 2013 ; Hohla et al, 2014 ; Sun et al, 2018 ; Lu et al, 2020 ; Zhao et al, 2020a ), which may provide insight into the molecular mechanisms underlying poor prognosis in the high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of Thyroid Hormones (THs) system in Colorectal Cancer (CRC) suggests that these hormones may play roles in CRC pathogenesis [ 47 ]. Morphine promotes tumorigenesis and cetuximab resistance via EGFR signaling activation in human colorectal cancer [ 48 ]. Glycolysis and glycine, serine and threonine were activated in CRC, and these alterations may promote cell proliferation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%